If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2a + 15 = 2a + 5z Reorder the terms: 15 + -2a = 2a + 5z Solving 15 + -2a = 2a + 5z Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-2a' to each side of the equation. 15 + -2a + -2a = 2a + -2a + 5z Combine like terms: -2a + -2a = -4a 15 + -4a = 2a + -2a + 5z Combine like terms: 2a + -2a = 0 15 + -4a = 0 + 5z 15 + -4a = 5z Add '-15' to each side of the equation. 15 + -15 + -4a = -15 + 5z Combine like terms: 15 + -15 = 0 0 + -4a = -15 + 5z -4a = -15 + 5z Divide each side by '-4'. a = 3.75 + -1.25z Simplifying a = 3.75 + -1.25z
| 2/3t-11=4(6-t)-1/3t | | j+.333333=.75 | | 12-45= | | 12x=280+4x | | 6y+12=4y+4 | | -7(6x-1)=-27-8x | | (X+12/x+2)-3=0 | | 5x+8=-x-40 | | 8.9=9.5-0.2x | | 16x^2+-5(7-x^2)+43=0 | | 66x+5=180 | | 3(8-6x)=96 | | 44/7/d=4/7 | | ((x-1)/3)=(-1/5) | | 2.5c+6.7=-1.3 | | 2x+4x-7=5 | | -(p+2)+4=38+8p | | -4(-1x+6)=-16 | | 9-(-2-3x)+4(-x+6)-x+12-3(2x-3)= | | 4-6x=32 | | -4(x+4)+4=6(x+3)+9 | | 5u-8=24 | | 1/10-2 | | -6x+5=-7-3x | | 3(4-j)=18 | | 14x^3-53x^2+41x-4=-4x^3+x^2+x+4 | | -6(5x-6)=96 | | -(4x-4)-(10x-6)+5=-5(x-1)-(13x+5)+3 | | 2/3+1/2=14 | | -(19+2g^2)+-57+4g^2=0 | | 8+4x=-6x-32 | | t^3-5t^2+9t=0 |